Software for automated reading of sunshine duration by Digital Image Processing - Raniero, M. R. [UNESP] (2020)
The present study aims to demonstrate the benefits and results obtained from software for filtering, processing and managing sunshine duration monitored by heliographs, in meteorological stations. The source code of the software was developed using the Java EE 7 (Java Enterprise Edition) programming language, based on internet applications. Information storage and management was performed by the MySQL 5.7 Database Management System (DBMS). Digital image processing techniques, incorporated in the software, allowed to count sunshine duration in an automated and standardized way, eliminating errors due to the complexity and subjectivity in the measurement observation, performed manually. Processing routines were implemented to apply filters in the spatial domain, enhancing digital images of sunshine data, to better identify parts of interest and ensure quality in the accounting process. For software validation, a set of September 2015 sunshine data, provided by the Lageado Meteorological Station of the School of Agricultural Sciences (UNESP) of Botucatu - SP, was used. In which, comparisons between readings performed by the computer program and readings performed manually showed MBE values of 0.130 hours (rMBE = 1.908%), RMSE of 0.259 hours (rRMSE = 3.791%) and R of 0.998. Indicating that the software can be used to read sunshine data, as it ensures automation, standardization and speed in the process.